עץ הזית: סמַּן אידאולוגי לכל עת בספרות העברית והישראלית - שחם, חיה (מכאן, 2016)
The olive tree has held a unique place in Hebrew and Israeli cultural discourse for at least nine decades (starting in the 1930s). This article attempts to map the significant metamorphoses of the olive tree as a symbol and ideological marker in Hebrew and Israeli literature. Apparently, its emblematic nature enables the olive tree to represent opposite entities over various periods in recent history and even within the same period itself, as has been the case over the last three decades. At first, the olive tree in Modern Hebrew literature was the symbol or metonym of Arab natives living in Eretz Yisrael. In the next stage it was appropriated by Hebrew writers as a symbol of the Zionist pioneers. Then, over the decades, the symbol was uprooted and re-planted time and again from one ideological territory to another. The ideological writing about the olive tree becomes very acute, especially in or after significant national events such as wars. Hence, the tree functions in Hebrew and Israeli literature mainly as a recurring marker of the ongoing conflict between Jews and Arabs over the territory of Eretz Yisrael. When examining the olive tree in Hebrew and Israeli literature, it transpires that it clearly acts as a litmus paper, revealing the writers’ political and ideological views.